2020
DOI: 10.1245/s10434-020-09026-z
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Interval Between Completion of Adjuvant Chemotherapy and Initiation of Radiotherapy Impact Clinical Outcomes in Operable Breast Cancer Patients?

Abstract: Purpose The aim of this study was to evaluate the impact of time to radiotherapy (TTR) after completion of chemotherapy (CT), and TTR after surgery, in breast cancer (BC) patients. Patients and Methods Continuous breast cancer patients treated with surgery and CT followed by radiotherapy (RT) from 2009 through 2015 were retrospectively reviewed. Patients were categorized into four groups with respect to TTR after CT, i.e. <4, 4–8, 8–12, and >12 weeks, and TTR after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…In our study population, the majority of patients started RT within 12 weeks after the last cycle of adjuvant chemotherapy or within 16 weeks after surgery when no adjuvant chemotherapy is given, which is consistent with previous reports (21)(22)(23). In a recent retrospective study of the impact of TTR on survival, among 95 patients treated with NAC without adjuvant chemotherapy, Xie et al (21) reported that 25 (26.3%), 54 (56.8%), and 16 (16.8%) started RT at <8 weeks, 8-16 weeks, and > 16 weeks from surgery, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In our study population, the majority of patients started RT within 12 weeks after the last cycle of adjuvant chemotherapy or within 16 weeks after surgery when no adjuvant chemotherapy is given, which is consistent with previous reports (21)(22)(23). In a recent retrospective study of the impact of TTR on survival, among 95 patients treated with NAC without adjuvant chemotherapy, Xie et al (21) reported that 25 (26.3%), 54 (56.8%), and 16 (16.8%) started RT at <8 weeks, 8-16 weeks, and > 16 weeks from surgery, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…However, evidences for acceptable interval from end of adjuvant chemotherapy to RT were limited (35,36). A recent study of 989 operable BC patients reported that the time to RT after chemotherapy over 12 weeks negatively impact 5-year distant recurrence free survival and breast cancer specific survival (37). Long-term follow-up is needed to assess the prognosis of patients who experienced RT interruption or FIGURE 2 | The hierarchical multiple regression model of fear of cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Raphael et al [16] reported that a CRI of 6 weeks was associated with worse event-free survival in patients with stage I and II breast cancer who underwent BCS (HR 1.50; 95% CI: 1.00e2.22). Cao et al [17] reported that a CRI of >12 weeks was associated with worse breast cancer-specific survival and OS in patients with stage IeIII breast cancer who underwent either BCS or mastectomy. In comparison, most patients in the present study had more advanced disease (97% being stage III), and all the patients underwent mastectomy.…”
Section: Discussionmentioning
confidence: 99%